2001
DOI: 10.1046/j.1365-2222.2001.01089.x
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Chinese translated version of ISAAC core questions for atopic eczema

Abstract: SummaryBackground The International Study of Asthma and Allergies in Childhood (ISAAC) was designed to allow international comparison of epidemiological data on atopic conditions in childhood. In so doing, further aetiological information would be obtained that in turn would provide a framework for future studies. The global ISAAC results on the prevalence of atopic dermatitis indicated a 60-fold variation recorded in different countries. Such a degree of difference may be partially due to the translated quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 20 publications
1
48
0
2
Order By: Relevance
“…Data used for analyses were collected retrospectively and relied on parental reports; our findings could therefore be subject to recall bias. A strength of the study is that core ISAAC questions have been validated [69] as have questions on indoor exposures [70,71]. Non-respondents were reached by a short survey in Chongqing.…”
Section: Discussionmentioning
confidence: 99%
“…Data used for analyses were collected retrospectively and relied on parental reports; our findings could therefore be subject to recall bias. A strength of the study is that core ISAAC questions have been validated [69] as have questions on indoor exposures [70,71]. Non-respondents were reached by a short survey in Chongqing.…”
Section: Discussionmentioning
confidence: 99%
“…Working Party [12][13][14][15][16][17] and the ISAAC diagnostic criteria 18,19 performed in many parts of the world have demonstrated their validity, although some have shown low sensitivity. 17,19 One study in Germany has suggested that cultural and educational factors could influence the universal application of such questionnaire-based criteria. 20 Our prime research goal was to investigate possible risk factors for AE in an urban and rural Ethiopian population.…”
Section: Discussionmentioning
confidence: 99%
“…The health problems of interest in this study were physician diagnosed asthma, AR and eczema and their related symptoms in the last 12 months, and diagnosed pneumonia. The ISAAC questionnaire has been previously used for Chinese children [1214] and validated by clinical investigation [15].…”
Section: Questionnairementioning
confidence: 99%